Treatment of spentwash using chemically modified bagasse and colour removal studies - Mane, Jyoti D.; Modi, Shewta; Nagawade, Swati; Phadnis, S. P.; Bhandari, Vinay M. (Bioresource Technology, 2006)
Studies were carried out on derivatisation of bagasse into an ion exchange material and application of this chemically modified bagasse in the treatment of distillery wastewater. It was found that CHPTAC bagasse with HCl treatment and DEAE-bagasse in its free base form were most effective in colour removal and the mechanism of colour removal indicated significant contribution of both, the conventional ion exchange and the chemical sorption. (c) 2005 Elsevier Ltd. All rights
Keywords: decolourisation; distillery effluent; modified biomass; vinasse

Ultrasound assisted synthesis of polyacrylic acid-nanoclay nanocomposite and its application in sonosorption studies of malachite green dye - Sonawane, S. H.; Chaudhari, P. L.; Ghodke, S. A.; Parande, M. G.; Bhandari, Vinay M.; Mishra, Satyendra; Kulkarni, R. D. (Ultrasonics Sonochemistry, 2009)
Synthesis of nanoclay nanocomposite has been undertaken by using polyacryalic acid (PAA) in aqueous medium and ultrasound environment and its application in dye removal has been investigated. The synthesized product was characterized by using FTIR and XRD techniques. The sonosorption capacity of the product namely PAA-nanoclay composite was determined by choosing malachite green (MG) dye as a model pollutant. The effects of various parameters such as nanocomposite loading, pH, various process conditions etc. have been studied. On comparing the results obtained with that of nanoclay as an adsorbent, it was found for an initial concentration of 500 mg/l, the PAA-nanoclay nanocomposite exhibited higher percentage of pollutant removal (68%) and for nanoclay it was 54%. The adsorption data has been correlated using Langmuir and Freundlich models. The fit of the Freundlich isotherm model was found to be good in the entire range of concentration for the experimental sorption data obtained on the nanoclay nanocomposite. A plausible reaction mechanism for use of PAA-nanoclay nanocomposite as ail adsorbent is also proposed. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Malachite Green; Nanocomposite; Polyacrylic acid; Sonosorption; Ultrasound

Development of newer adsorbents: activated carbons derived from carbonized cassia fistula - Sorokhaibam, Laxmi Gayatri; Bhandari, Vinay M.; Salvi, Monal S.; Jain, Saijal; Hadawale, Snehal D.; Ranade, Vivek V. (Industrial & Engineering Chemistry Research, 2015)
Development of newer adsorbent materials, especially from biomass, is most crucial to sustain growth of otherwise well established adsorption processes that already have hundreds of commercial adsorbents in practice. In the present study, newer adsorbents and their potential-carbonaceous adsorbents derived from the whole fruit of Cassia fistula (Golden shower) have been reported for applications in environmental pollution control using natural, renewable biomass as precursor. The potential of different forms of the derived adsorbents produced by thermal and chemical activation was examined for two representative cases, desulfurization of transportation fuels and wastewater treatment. The adsorbents were characterized by FTIR, XRD, XPS, and SEM techniques that indicate specific characteristics useful as an adsorbent. A successful application in the real industrial wastewater treatment and comparison with well recognized commercial adsorbents clearly highlights the utility of the developed newer adsorbents in separation science and technology.

Differentiating process performance of various coagulants in removal of congo red and orange G dyes - Prajapati, Kavita; Sorokhaibam, Laxmi Gayatri; Bhandari, Vinay M.; Killedar, D. J.; Ranade, Vivek V. (International Journal of Chemical Reactor Engineering, 2016)
Two refractory azo dyes-Congo red and Orange G, especially at high concentrations were subjected to coagulation with different conventional coagulants and newer formulations developed from Aluminum sulfate, Iron (III) chloride, Aluminium chloride, Poly diallydimethylammonium chloride (Poly DADMAC) and Poly Aluminium Chloride (PAC). The highest COD reduction of 99 % was obtained with PAC SAB 18 (Powder Grade PAC) for Congo red at pH 4.5 while the color removal of 99 % was achieved with almost all the coagulants in the present study at specific pH within 3-8. The optimum dose for the iron-based coagulant is 200 mg/L while that of aluminum-based coagulants and PAC is 150-200 mg/L. Results showed that Orange G was more difficult to remove with a maximum COD removal of 65 % and 35 % color removal using various formulations. The combinational formulations of inorganic-inorganic and inorganic- organic produced a substantial enhancement in COD and color removal and reduced sludge. PAC-Fe30/70 produces the minimum sludge of 50 mL/g on Congo red. pH in the range 3-9 showed high reductions in COD and color (90-99 %) for Congo red while jerky rise in COD and color reduction was observed in the case of Orange G after pH 9. An attempt to understand the dye coagulation mechanism has been made based on the specific difference in dye structure and cation speciation.
Keywords: coagulation; Congo red; dye removal; Orange G; Wastewater treatment

Green approach to dye wastewater treatment using biocoagulants - Chethana, M.; Sorokhaibam, Laxmi Gayatri; Bhandari, Vinay M.; Raja, S.; Ranade, Vivek V. (ACS Sustainable Chemistry & Engineering, 2016)
The present study focuses on newer biocoagulants, bioformulations, and the understanding of coagulant behavior with biocoagulants in relation to chemical coagulants. Newer biocoagulants, seeds of Azadirachta indica (AI) and pads of Acanthocereus tetragonus, are discussed along with two known biocoagulants, Moringa oleifera and Cicer arietinum seeds. Dye removal studies were carried out using widely reported Congo red dye to facilitate easy comparison with other conventional coagulants and the effect of various parameters such as initial dye concentration, pH, coagulant dose, etc. are discussed in detail. The use of biocoagulant was found to be highly effective, and up to 99% dye removal was achieved for coagulant doses in the range of 300-1500 mg/L. It was also observed that coagulation is pH sensitive, similar to chemical coagulants. Although the biocoagulant dose is relatively higher than the conventional chemical coagulants, a good value for the sludge volume index, similar to 50 mL/g for 1 h and 30 min, respectively, was obtained for the two coagulants, Acanthocereus tetragonus and Moringa oleifera. A very high particle count compared to chemical coagulants was observed using a focused beam reflectance measurement. Bioformulation with chemical coagulants such as alum, ferric, and aluminum based coagulants can, not only lower doses of biocoagulants (up to one-third) but can also result in significant improvement in the coagulation performance, up to 50% or more.
Keywords: coagulation; dye removal; Effluent treatment; flocculation; pollution

Industrial wastewater treatment for fertilizer industry a case study - Bhandari, Vinay M.; Sorokhaibam, Laxmi Gayatri; Ranade, Vivek V. (Desalination and Water Treatment, 2016)
Wastewaters from chemical fertilizer industry mainly contain organics, alcohols, ammonia, nitrates, phosphorous, heavy metals such as cadmium and suspended solids. The nature of effluent streams varies in terms of its constituents and complexity. The present work attempts to fill the void in the literature that mostly reports synthetic wastewater treatment studies, by evaluating effluent treatment solutions and comparison of different methods for real wastewaters from the fertilizer industry. An attempt has been made to devise suitable methodology mainly using a new device in the form of vortex diode for hydrodynamic cavitation and also using adsorption, for several real wastewater streams from different locations in one major fertilizer industry of Maharashtra, India. The strategy involved characterization of wastewaters, studies on the effective removal of chemical oxygen demand (COD) and devising solutions for effective reduction in ammoniacal nitrogena more serious issue in the fertilizer industry. The characterization of wastewaters from different streams revealed huge variation in COD from 50 to 140,000ppm and ammoniacal nitrogen from 6 to 1,700ppm. Some effluent streams contained alcohol up to 5%. Hydrodynamic cavitation using vortex diode and adsorption with modified carbons were used to treat these streams. Cavitation studies were carried out on a pilot plant and the effect of pressure drop, cavitating device and process intensification were studied. It was observed that the effluent treatment strategy requires careful identification and application of suitable treatment method on the basis of the nature of the effluent. Also, hydrodynamic cavitation, using vortex diode appears to be techno-economically attractive option in treating fertilizer wastewaters giving a very high reduction in COD and ammoniacal nitrogen (up to 85%), similar to adsorption. The results clearly identify potential of newer methodologies in the treatment of effluents in the fertilizer industry.

Non-catalytic deep desulphurization process using hydrodynamic cavitation - Suryawanshi, Nalinee B.; Bhandari, Vinay M.; Sorokhaibam, Laxmi Gayatri; Ranade, Vivek V. (Scientific Reports, 2016)
A novel approach is developed for desulphurization of fuels or organics without use of catalyst. In this process, organic and aqueous phases are mixed in a predefined manner under ambient conditions and passed through a cavitating device. Vapor cavities formed in the cavitating device are then collapsed which generate (in-situ) oxidizing species which react with the sulphur moiety resulting in the removal of sulphur from the organic phase. In this work, vortex diode was used as a cavitating device. Three organic solvents (n-octane, toluene and n-octanol) containing known amount of a model sulphur compound (thiophene) up to initial concentrations of 500 ppm were used to verify the proposed method. A very high removal of sulphur content to the extent of 100% was demonstrated. The nature of organic phase and the ratio of aqueous to organic phase were found to be the most important process parameters. The results were also verified and substantiated using commercial diesel as a solvent. The developed process has great potential for deep of various organics, in general, and for transportation fuels, in particular.

Elucidating efficacy of biomass derived nanocomposites in water and wastewater treatment - Kirti, Saumaya; Bhandari, Vinay M.; Jena, Jyotsnarani; Bhattacharyya, Arnab S (Journal of environmental management, 2018)
In the present study, two synthesis methods of nanocomposites-one involving a mixture of biomass and the other using chemical modification were investigated to evaluate practical application of green approach in pollution control, specifically for water and wastewater treatment. Newer multifunctional superparamagnetic nanocomposites using biomaterials such as unripened fruit of Cassia fistula (Golden shower) and Aloe vera were developed as an example of green approach while chemical modification was illustrated using n-octanol. Two specific model applications were studied for the developed materials-dye removal (Methyl Blue and Congo Red) and disinfection-demonstrating antimicrobial property. To elucidate the multifunctional character, the texture, morphology and composition of the prepared bionanocomposites were studied. The surface area values were 6.2 and 9.8 m(2)/g for Aloe vera and octanol based nanocomposites while the average pore diameters were 1.79 nm and 5.7 nm respectively, indicating presence of highly developed micropores in the first material having a honeycomb shape and the later showing excellent staircase type formation with larger pores. A very high dye removal to the extent of 100% was obtained that can be attributed largely to the functionalities imparted from Cassia fistula compared to ingredients from Aloe vera and octanol. The nanomaterials could be completely separated with absolute ease by applying simple magnetic field. Also, successful application of the developed materials in disinfection, removal of E. coif, was demonstrated with a very high efficiency of over 95%. The biomass derived nanocomposites exhibit excellent pollutant removal and disinfection properties, even at very low nanoparticle content; octanol based material indicating similar to 5 times lowered cost, while the Aloe vera based bionanocomposites have potential for cost reduction to the extent of 10 times as compared to only magnetite nanoparticles, thereby highlighting techno-economical alternative in water and wastewater treatment.

Exploiting functionalities of biomass in nanocomposite development: application in dye removal and disinfection along with process intensification - Kirti, Saumaya; Bhandari, Vinay M.; Jena, Jyotsnarani; Sorokhaibam, Laxmi Gayatri; Bhattacharyya, Arnab S. (Clean Technologies and Environmental Policy, 2018)
A green synthesis of multifunctional superparamagnetic nanocomposites using the whole unripened fruit of Cassia fistula (Golden shower) with potential for removal of both cationic and anionic dyes and antimicrobial property is reported for the first time in the present work. A natural medium in the form of clarified butter was used to enhance the multifunctional character. The surface morphology, textural characteristics and composition of the prepared nanoparticles and composites were studied to understand the multifunctional nature. The dye removal was investigated for four different dyes, namely methyl blue, Congo red, rhodamine-B and auramine. Iron nanoparticles were largely effective in the removal of acidic dyes, while the magnetic nanocomposites were effective for the removal of both acidic and basic dyes which can be attributed to the functionalities imparted from Cassia fistula and clarified butter. The dye removal behavior can be significantly enhanced (similar to 50%) using process intensification-adsorption coupled with acoustic cavitation, which also indicated a reduced adsorbent loading as compared to the conventional adsorptive dye removal. The nanomaterials were completely separated from dye solution with absolute ease of separation by applying simple magnetic field. Also, the developed materials were useful in disinfection of E. coli with a high efficiency of 90% confirming significant antimicrobial property at lower concentrations.

Multifunctional activated carbon with antimicrobial property derived from Delonix regia biomaterial for treatment of wastewater - Louis, Mary R.; Sorokhaibam, Laxmi Gayatri; Bhandari, Vinay M.; Bundale, Sunita (Journal of Environmental Chemical Engineering, 2018)
In this work, we report the development of a multifunctional high surface area activated carbon (DRP), from a biomaterial, Delonix regia, with antimicrobial potential and demonstrated its applicability towards removal of two reactive dyes, Reactive Red (RR-120) and Reactive Blue (RB-4) with an adsorption capacity of ∼6.36 and 24 mg·g−1 respectively. The newer multifunctional activated carbon was prepared from the deseeded pods of Delonix regia through thermo-chemical surface modification and characterized for surface and morphological characteristics, chemical composition, and thermal stability. DRP exhibited a high surface area of 1577 m2·g−1 with various active functional groups. The decolourisation efficiency achieved was very high, ∼98% for both the dyes. The effects of various operating parameters like pH, initial dye concentration, adsorbent dosage, surfactant, salt etc. were investigated and the batch adsorption equilibrium data in each dye system was analyzed with various isotherms-Langmuir, Freundlich, and Tempkin. The kinetics of the adsorption process was best represented by pseudo-second order kinetic model and the adsorption efficiency was also illustrated in the binary system of varying dye compositions. DRP could successfully reduce the microbial growth of Gram positive B. subtilis with a higher zone of inhibition.

Solvent degradation studies using hydrodynamic cavitation - Suryawanshi, Pravin G.; Bhandari, Vinay M.; Sorokhaibam, Laxmi Gayatri; Ruparelia, Jayesh P.; Ranade, Vivek V. (Environmental Progress & Sustainable Energy, 2018)
Hydrodynamic cavitation for the degradation of organic solvents was investigated in detail using a newer form of cavitating device-vortex diode. The results were also compared with that using conventional cavitating device orifice. Removal of three different organic solventsacetone, methyl ethyl ketone (MEK), and toluene were studied on a pilot plant with capacity of 1m(3)/h. The effect of different operating parameters such as inlet pressure, initial concentration, and reactor type on the degradation rate of solvent was investigated in detail. The results revealed that efficiency of solvent removal varies substantially with the change in physical operating conditions and nature of the solvent. It was found that up to 80% degradation could be achieved for toluene (cavitational yield 32.2 x 10(-3) mg/J), substantially higher than that for acetone and MEK indicating the effect of molecular weight/structure in the degradation process. Further, the results clearly indicated chemical oxidation as a predominant mechanism for degradation and not physical destruction. Vortex diode that works on the principle of vortex generation for cavitation, was found to be far superior over conventional cavitating device-orifice- approximate to up to eight times higher cavitational yield could be obtained for toluene as compared to orifice. The results of this study provide newer insight into solvent removal using hydrodynamic cavitation and would have bearing on the treatment of solvent containing wastewaters. (C) 2017 American Institute of Chemical Engineers
Keywords: Effluent treatment; industry; pollution; Vortex diode; wastewater

Hydrodynamic cavitation using vortex diode: an efficient approach for elimination of pathogenic bacteria from water - Jain, Pooja; Bhandari, Vinay M.; Balapure, Kshama; Jena, Jyotsnarani; Ranade, Vivek V.; Killedar, Deepak J. (Journal of Environmental Management, 2019)
The present study successfully demonstrates greener methodology of hydrodynamic cavitation using rotational flows for disinfection of water. Disinfection of two model microbial strains-gram-negative (Escherichia colt) and gram-positive (Staphylococcus aureus) using vortex diode was evaluated. The removal efficacy was quantified for two different cavitation reactors. Practically complete elimination of E. coli was achieved (99%) after 1 h of cavitation at a pressure drop of only 0.5 bar. However, elimination of S. aureus using vortex diode was observed to be lower in comparison to the removal of E. coli and only 60% disinfection could be achieved under similar conditions, which can be subsequently enhanced up to 98% by increasing pressure drop. The results were compared with another cavitating device that employs linear flow for cavitation, orifice. The reactor geometry has significant impact on the disinfection process and orifice was found to require significantly higher pressure drop (10 bar) conditions for disinfection and for eliminating grain-positive bacteria with high efficiency. A plausible mechanism for disinfection was proposed to elucidate the role of cavitation in cell destruction leading to death of cells through the rupture of cell wall, oxidative damage and possible DNA denaturation. Also, a cavitation model using per pass disinfection was developed that can provide meaningful physical description of the disinfection process as against the conventional first order reaction rate model. This study would provide meaningful insight into cavitation process based on hydrodynamic cavitation for the destruction of both gram-negative and gram-positive bacteria from various water sources, including industrial wastewaters.
Keywords: Cavitation; Disinfection; kinetics; pollution; Wastewater treatment

Destroying antimicrobial resistant bacteria (AMR) and difficult, opportunistic pathogen using cavitation and natural oils/plant extract - Mane, Maya B.; Bhandari, Vinay M.; Balapure, Kshama; Ranade, Vivek V. (Ultrasonics Sonochemistry, 2020)
The present study reports, for the first time, a new and techno-economic strategy for effective removal of antimicrobial resistant bacteria (AMR) and difficult, opportunistic pathogen using cavitation and natural oils/plant extract. A hybrid methodology using natural oils of known health benefits has been discussed in combination with conventional physico-chemical method of hydrodynamic cavitation that not only provides efficient and effective water disinfection, but also eliminates harmful effects of conventional methods such as formation of disinfection by-products apart from reducing cost of treatment. A proof-of concept is demonstrated by achieving exceptionally high rates for practically complete removal of antimicrobial resistant (AMR) and relatively less researched, gram-negative opportunistic pathogen, Pseudomonas aeruginosa and gram-positive methicillin resistant, Staphylococcus aureus using a natural oil-Peppermint oil and two different cavitating reactors employing vortex flow (vortex diode) and linear flow (orifice) for hydrodynamic cavitation. > 99% disinfection could be obtained, typically in less than 10 min, using vortex diode with operating pressure drop of 1 bar and low dose of 0.1% peppermint oil as an additive, depicting very high rates of disinfection. The rate of disinfection can be further increased by using simple aeration which can result in significant lowering of oil dose. The conventional device, orifice requires relatively higher pressure drop of 2 bar and comparatively more time (similar to 20 min) for disinfection. The cost of the disinfection was also found to be significantly lower compared to most conventional processes indicating techno-economic feasibility in employing the developed hybrid method of disinfection for effectively eliminating bacteria including AMR bacteria from water. The developed approach not only highlights importance of going back to nature for not just conventional water disinfection, but also for eliminating hazardous AMR bacteria and may also find utility in many other applications for the removal of antimicrobial bacteria.
Keywords: AMR bacteria; Cavitation; Disinfection; Oil; Water treatment

Novel hybrid cavitation process for enhancing and altering rate of disinfection by use of natural oils derived from plants - Mane, Maya B.; Bhandari, Vinay M.; Balapure, Kshama; Ranade, Vivek V. (Ultrasonics Sonochemistry, 2020)
The present study is an attempt to improvise the hydrodynamic cavitation methodology for effective disinfection of water and also to suggest prototype development for practical application. The enhancement in the disinfection efficiency was evaluated specifically for the effect of pressure, temperature, pH, microbial inoculum size and also on effect of different additives for the two model microbial strains, gram-negative (Escherichia coli) and gram-positive (Staphylococcus aureus). The efficacy of the hydrodynamic cavitation is evaluated for the two types of flows/cavitation devices - linear flow in the case of orifice and vortex flow for vortex diode. The vortex diode requires significantly lower pressures, 50% lower as compared to orifice for the similar extent of disinfection. While the bacterial disinfection at high temperature is known, the usefulness of hydrodynamic cavitation is especially evident at ambient conditions and the process is effective even at very high concentrations of bacteria, not reported so far. The reactor geometry also has significant effect on the disinfection. The present study, for the first time, reports possible use of different natural oils such as castor oil, cinnamon oil, eucalyptus oil and clove oil in conjunction with hydrodynamic cavitation. The nature of oil modifies the cavitation behavior and an order of magnitude enhancement in the cavitation rate was observed for the two oils, eucalyptus and clove oil for a very small concentration of 0.1%. The increased rates of disinfection, of the order of 2-4 folds, using oil can drastically reduce the time of operation and consequently reduce cost of disinfection. A possible mechanism is proposed for the effect of oil and hydrodynamic cavitation in cell destruction through the rupture of cell wall, oxidative damage and possible DNA denaturation. A cavitation model using per pass disinfection was used to correlate the data. The increased efficiency using oils and possible benefits of the developed process, where natural oils can be perceived as biocatalysts, can have significant advantages in practical applications.
Keywords: Antimicrobial; Cavitation; Disinfection; Oil; Wastewater treatment

Improving efficiency for removal of ammoniacal nitrogen from wastewaters using hydrodynamic cavitation - Patil, Pravin B.; Bhandari, Vinay M.; Ranade, Vivek V. (Ultrasonics Sonochemistry, 2021)
The present study reports significant improvements in the removal of ammoniacal nitrogen from wastewater which is an important problem for many industries such as dyes and pigment, distilleries and fisheries. Pilot plant studies (capacity, 1 m(3)/h) on synthetic wastewater using 4-amino phenol as model nitrogen containing organic compound and two real industrial effluents of high ammoniacal nitrogen content were carried out using hydrodynamic cavitation. Two reactor geometries were evaluated for increased efficiency in removal-orifice and vortex diode. Effect of initial concentration (100-500 mg/L), effect of pressure drop (0.5-5 bar) and nature of cavitating device (linear and vortex flow for cavitation) were evaluated along with effect of salt content, effect of hydrogen peroxide addition and aeration. Initial concentration was found to have significant impact on the extent of removal: similar to 5 g/m(3) removal for initial concentration of 100 mg/L and up to 12 g/m(3) removal at high concentration of 500 mg/L. Interestingly, significant improvement of the order of magnitude (up to 8 times) in removal of ammoniacal nitrogen could be obtained by sparging air or oxygen in hydrodynamic cavitation and a very high removal of above 80% could be achieved. The removal of ammoniacal nitrogen by vortex diode was also found to be effective in the industrial wastewaters and results on two different effluent samples of distillery industry indicated up to 75% removal, though with longer time of treatment compared to that of synthetic wastewater. The developed methodology of hydrodynamic cavitation technology with aeration and vortex diode as a cavitating device was found to be highly effective for improving the efficiency of the conventional cavitation methods and hence can be highly useful in industrial wastewater treatment, specifically for the removal of ammoniacal nitrogen.
Keywords: Amino phenol; Cavitation; Oxidation; pollution; Wastewater treatment

Safe water and technology initiative for water disinfection: application of natural plant derived materials - Mane, Maya B.; Bhandari, Vinay M.; Ranade, Vivek V. (Journal of Water Process Engineering, 2021)
Safe drinking water is the necessity of life. The present study reveals use of natural resources such as plant extracts and natural oils for water disinfection. Differences between oil and water soluble additives were highlighted for plant extracts and insoluble natural oils. A hybrid hydrodynamic cavitation process was quite effective in both the cases and high rates of disinfection were achieved. Studies were reported using oils (ginger, turmeric, lavender, tulsi) and rhizome derived plant extracts such as ginger, turmeric and mango ginger, as additives in process intensification (0.1% v/V). A vortex based cavitation device (vortex diode, nominal capacity 1 m3/h) was used with pressure drop of 1 bar. A high disinfection of 96% and 88% was obtained in 15 min for ginger oil and mango ginger extract respectively as compared to 44% using cavitation alone. Acoustic cavitation gave 94% and 30% disinfection with and without additive-mango ginger extract. The FTIR analyses before and after cavitation, with ginger additive, showed no by-products formation and indicated gingerol as active component in disinfection. The per-pass disinfection values were also higher, up to 5 times than cavitation alone. Hybrid hydrodynamic cavitation using natural plant derived materials can offer a promising technology alternative in water disinfection.
Keywords: Cavitation; Disinfection; Natural oil; Plant extract; Water treatment

Wastewater treatment and process intensification for degradation of solvents using hydrodynamic cavitation - Patil, Pravin B.; Bhandari, Vinay M.; Ranade, Vivek V. (Chemical Engineering and Processing-Process Intensification, 2021)
Industrial wastewater treatment for removal of small concentrations of harmful solvents is pertinent issue in many chemical and pharmaceutical industries. The present work evaluates removal of three common solvents by hydrodynamic cavitation (nominal capacity, 1m(3)/h). Solvent degradation of three solvents viz. octanol, dimethyl formamide and cyclohexanol was studied in the concentration range of 50-200 mg/L and for the pressure drop range of 0.5-5 bar. The vortex based cavitation device (vortex diode) was compared with that of linear flow based device (orifice). Process intensification in the form of aeration and addition oxidizing agent-hydrogen peroxide was also evaluated for synergistic effect. The vortex diode required lower pressure drop and is superior to orifice and process intensification using aeration is most effective. A reduction in TOC to the extent of 74% could be achieved for octanol (200 ppm) using aeration with cavitational yield of 1202x10(-4) mg/J for vortex diode, yield similar to 10 times of orifice. The degradation depends on the nature of solvent and it was revealed that low values of dielectric constant (epsilon<10) favour degradation. The kinetics was evaluated using rate model based on per-pass degradation factor. The process techno-economic feasibility is useful in industrial wastewater treatment.
Keywords: Cavitation; Effluent; Organics removal; Oxidation; pollution

Design of hydrodynamic cavitation assisted intensified tertiary treatment unit for effective degradation of organic micropollutants in pharmaceutical industrial effluent: a case study with triclosan - Mishra, Birupakshya; Mukherjee, Anupam; Mullick, Aditi; Bhandari, Vinay M.; Moulik, Siddhartha (Journal of Water Process Engineering, 2022)
Increasing occurrence of micropollutants and trace amount of persistent organic contaminants (POC's) in the wastewater streams even after the well-established conventional treatment is a threat to human health, aquatic entities, and constitute a formidable challenge for the ecological security. In this regard, hydrodynamic cavi-tation based advanced oxidation treatment has attracted extensive attention towards removal of such micro scale pollutants from wastewater streams in the present scenario. Hence, the present work demonstrates the design and application of a rotating hydrodynamic cavitation (RHC) reactor with stator-rotor arrangement for effective degradation of organic micropollutants (triclosan being taken as the target pollutant) from tertiary effluents occurring in the pharmaceutical sector. The process performance was evaluated through optimization of geo-metric parameters of the reactor, various operating parameters as well as by studying the sole and synergistic performance of the HC process combined with other AOPs. The maximum degradation of Triclosan (TCS) ach-ieved by RHC alone was found to be 35.2 % and in synergism, with ozone, a maximum of 97.6 % degradation was observed. Further, to ensure the mineralization of the components, total organic carbon (TOC) contents of the samples were measured and the degradation pathway was predicted through LC-MS analysis. The techno-economic feasibility of the process were understood through economic and energetic analysis and technology transfer was done for replicating the same study for a pilot scale reactor.
Keywords: Advanced oxidation process; Hydrodynamic cavitation; Micropollutant; Pharmaceutical effluent; Tertiary treatment

Intensified hydrodynamic cavitation using vortex flow based cavitating device for degradation of ciprofloxacin - Patil, Pravin B.; Thanekar, Pooja; Bhandari, Vinay M. (Chemical Engineering Research & Design, 2022)
The present work, for the first time, establishes degradation behavior of ciprofloxacin (CIP), a widely used fluoroquinolone group of antibiotics, using vortex flow based hydro-dynamic cavitation (HC) for low to high concentrations of CIP (10 and 100 mg/L). Effect of pressure on the degradation of CIP and TOC reduction was investigated on pilot plant scale (capacity 1 m3/h). Process intensifications using aeration as well as hydrogen per-oxide (H2O2) were also investigated. While aeration did not yield any significant en-hancement, process intensification using H2O2 resulted in similar to 200% enhancement in the CIP degradation as compared to HC alone. Excellent degradations, to an extent of 79 & 95%, were achieved corresponding to high cavitational yields of 7.2 x 10-4 mg/J and 86.8 x 10-4 mg/J for CIP concentrations of 10 and 100 mg/L respectively using the process intensified approach of HC and H2O2, not reported so far for cavitating devices without moving ele-ments. The developed methodology demonstrated 4-7 times improvement in per-pass degradation and low cost with high efficiency compared to the conventional cavitation. The results clearly highlight utility of the process intensified approach using H2O2 for the degradation of CIP even at high concentrations, specifically important for pharmaceutical industries requiring zero liquid discharge norms.(c) 2022 Institution of Chemical Engineers. Published by Elsevier Ltd. All rights reserved.
Keywords: Antibiotics removal; ciprofloxacin; Degradation; Oxidation; Wastewater treatment

Solvent-assisted cavitation for enhanced removal of organic pollutants - degradation of 4-aminophenol - Patil, Pravin B.; Bhandari, Vinay M. (Journal of Environmental Management, 2022)
A new approach of solvent-assisted cavitation process was proposed for degradation of organic pollutants. The process envisages the use of suitable solvent as an additive, (1-5% v/V), in the conventional cavitation process to enhance the pollutant removal efficiency. A proof of concept was provided for the removal of ammoniacal nitrogen with significantly improved efficiency using solvent-assisted hydrodynamic cavitation (HC) compared to conventional HC. The efficacy of the process was studied on a pilot plant scale (1 m(3)/h) and using vortex flow based vortex diode as a cavitating device. Degradation studies were carried out using a model pollutant, 4-amino phenol and four different solvents as additives, 1-octanol, cyclohexanol, 1-octane and toluene. Relatively polar solvents were found to increase the efficiency of the pollutant removal (> 65%) and also increase the rates to an extent of more than 200%, compared to only HC. A very high removal of ammoniacal nitrogen, more than 90%, was obtained for solvents 1-octanol and cyclohexanol, indicating the importance of the selection of solvent. Per pass degradation model showed 3 to 4 times increase in the per pass degradation for polar solvents compared to cavitation alone. The results confirm no role of conventional solvent extraction and no specific contamination of wastewater due to the use of solvent as an additive in the process. Further, the cost was 2-3 times lower as compared to the conventional HC. The interesting observations in the proposed process can fuel further research to provide possible improvements in existing methodologies of wastewater treatment, in general, and for removal of ammoniacal nitrogen, in particular.
Keywords: Ammoniacal nitrogen; Hydrodynamic cavitation; Oxidation; Pollution Control; Wastewater treatment

Studies in instant water disinfection using natural oils - Dixit, Divya; Bhandari, Vinay M.; Mane, Maya B.; Balapure, Kshama (Biochemical Engineering Journal, 2022)
The present research reveals an instant and simple process for drinking water treatment by employing specific natural oils having antimicrobial properties to ensure complete elimination of harmful bacteria. The disinfection was studied for two different model bacteria, Gram-negative E. coli and Gram-positive, S. aureus. Seven natural oils, ajwain, thyme, oregano, peppermint, harsingar, cinnamon leaf and black pepper oil were evaluated and were found to yield 100% water disinfection within 1 min except for harsingar and black pepper oil. The process was also effective for the instant and 100% disinfection of real well water. The methodology for altering zeta potential, to an extent of 130%, for instant disinfection in drinking water treatment helps in selecting natural oils. Molecular docking studies indicated natural oils action as potential inhibitors of bacterial DNA gyrase. The studies indicate one of the lowest operating costs comparable to conventional chlorination. The simple meth-odology not requiring complex equipment has the potential to provide many options for implementations-from portability, household application to large scale water treatment plants.
Keywords: Bacteria removal; Natural oil; Technology; Water treatment; Zeta potential

Sustainable fabrication of copper nanoparticles: a potent and affordable candidate for water treatment, water disinfection, antioxidant activity and theranostic agent - Sinha, Tanur; Adhikari, Partha Pradip; Bhandari, Vinay M. (ChemistrySelect, 2022)
This study reports a simple, green, and large-scale biosynthetic fabrication of spherical copper nanoparticles (Cu NPs), approximate 28 nm, using the aqueous extracts of Diaplazium esulentum (Retz.) Sw. fern. Characterization was carried out for morphology, size, elemental analysis, crystallinity and for identification of functionalities responsible for reduction and stabilization. Extraordinary remediation efficiency was obtained for the developed Cu NPs for the elimination of two industrially important pollutants; Methyl Violet 6B and Methylene Blue (greater than 92 % within 150 mins). A mechanism was postulated for the process using the data on the identification of NPs and also spent NPs apart from degraded products. Furthermore, the Cu NPs revealed excellent antibacterial activity against gram positive bacteria: Staphylococcus aureus, Streptococcus pneumonia and Bacillus subtilis, as well as gram negative bacteria: Pseudomonas aeruginosa, Escherichia coli and potential action against fungal strains; Aspergillus niger and Candida albicans. Additionally, the assay depicted that Cu NPs has fairly decent radical scavenging activity with IC50 value 2.11 mM. Moreover, the Cu NPs were found to exhibit profound anticancerous activity against two human cancer line cells. The present research work has implications for exploitation of DE fern extract for the development of Cu NPs and their numerous applications ranging from pollutants removal to antibacterial, antifungal, antioxidant and anticancerous agents.
Keywords: Anticancer; antifungal; Antimicrobial; Antioxidant; Photodegradation and Phytosynthesis

Development of multipurpose biomass-derived adsorbents using Coccinia grandis for removal of contaminants - Raj, Surabhi S.; Mane, Maya B.; Thanekar, Pooja; Balapure, Kshama; Bhandari, Vinay M. (Clean Technologies and Environmental Policies, 2023)
The present study is an attempt to develop newer multipurpose biomass-derived adsorbents for water and wastewater treatment; biomass that are easily available, renewable and most importantly, sustainable. A model adsorbent was developed using Coccinia grandis (CG, Ivy gourd) and further modified by impregnating copper nanoparticles (CG-Cu). The adsorbent characterization was done for evaluating surface morphology, surface area and metal modification. The utility of the newer adsorbents was established for the removal of different contaminants such as dyes (cationic Malachite Green, anionic Congo Red and fluorescent cationic Rhodamine B), Active Pharmaceutical Ingredient pollutant (Ciprofloxacin) and also for the removal of pathogenic bacteria, Gram-negative Escherichia coli. Both CG and CG-Cu bio-nanocomposite were highly effective in removal of different contaminants, 99% dye removal for Malachite Green, with a high adsorption capacity of 49 mg/g, higher than that for commercial activated charcoal whereas for all other dyes, the performance of CG-Cu was similar. The isotherm studies indicated multilayer adsorption, in general. A good adsorption capacity of 10.8 mg/g was also observed for the removal of ciprofloxacin. The combined effect of the bio-nanocomposite, CG-Cu was impressive and 100% disinfection was achieved within 10 min, due to the antimicrobial activity of Cu and oxidation effect of reactive oxygen species enhancing the disinfection.Graphical abstractMultipurpose biomass derived adsorbents using Coccinia grandis for removal of contaminants
Keywords: Adsorption; Biomass; Disinfection; dye removal; nanomaterial; Separation

Dual activity cavitation reactors for increased efficacy in degradation of refractory pollutants-A case study on cephalexin degradation - Dixit, Divya; Thanekar, Pooja; Bhandari, Vinay M. (Chemical Engineering Research & Design, 2023)
The present work discloses a new form of cavitation processes using reactors of dual activity for increased efficiency. A proof of concept is established for the degradation of a refractory pollutant-cephalexin using both conventional and dual function cavitation reactors for the first time using acoustic and hydrodynamic cavitation (HC). A vortex diode as a cavitating device was employed for HC using aluminium as a non-catalytic and copper as dual function device for providing additional catalytic effect. The process in-tensification using hydrogen peroxide (H2O2) coupled with the dual function devices was highly effective. A negligible degradation with only HC and 81% for HC coupled with H2O2 in 60 min for Al-vortex diode compared to 100% degradation in only 5 min for the copper device clearly demonstrates the order of magnitude enhancements establishing dual function due to catalytic activity. Also, pH modification (pH 11) yields enhancement over 300% for Cu-vortex diode. The use of dual function reactors drastically reduces H2O2 do-sage. The overall enhancements in the per pass degradation and cavitation yields were huge, similar to 3000% and 1450% respectively, highlighting the potential of the dual function ca-vitation reactors in real-life applications, not just for increased efficiencies but also for significantly reduced costs.(c) 2023 Institution of Chemical Engineers. Published by Elsevier Ltd. All rights reserved.
Keywords: Advanced oxidation; Degradation; pollution; Technology; Wastewater treatment

Enhanced degradation of metformin using surface-coated vortex diodes - Dixit, Divya; Thanekar, Pooja; Bhandari, Vinay M. (Chemical engineering and processing-process intensification, 2023)
The present work successfully demonstrates, for the first time, complete degradation of metformin using newer surface-coated vortex diode (SCVD) with copper and nickel coating to provide catalytic activity in the conventional hydrodynamic cavitation (HC) for significantly enhanced degradation efficiency. The SCVDs have dual functionality and the efficacy of catalytic cavitation reactors get enhanced using process intensifications of the type H2O2 addition, pH modification, and combined approach of HC+ pH+ H2O2 apart from the advantage of low pressure drop for the vortex flow based cavitation in vortex diode (Delta P of 1 bar). Complete, 100%, degradation of metformin (MTF) was achieved within 5 min with integration of optimized H2O2 dose and exceptionally high synergistic index value over 300, indicating extraordinary synergy for both Cu and Ni-SCVD. Acidic condition promote degradation and a complete degradation with a high 43-48% mineralization was observed using HC+ pH 4+ (1:200) H2O2 with less intermediates formation. The SCVDs reveal remarkable enhancement of similar to 9800% in per-pass degradation and 1400-3400% in cavitational yield as compared to conventional cavitation process under similar conditions. The newer SCVDs with catalytic activity can provide more cost-effective solutions for industrial and real-life applications.
Keywords: Cavitation; Oxidation; pollution; Technology; Wastewater treatment

Improving hydrodynamic cavitation using newer surface-coated cavitation reactors - Dixit, Divya; Thanekar, Pooja; Bhandari, Vinay M. (Chemical Engineering Research & Design, 2023)
Surface-coated cavitation devices, vortex diode (SCVD) have been reported for the first time for enhancing efficiency of hydrodynamic cavitation (HC). Two surface-coated cavitation reactors using coating of copper and nickel (-50 mu m) were evaluated, also comparing results with conventional reactor vortex diode. The proof of concept is successfully demonstrated for complete degradation of two model organic pollutants, antibioticscephalexin (CFX) and ciprofloxacin (CIP). The surface-coated reactors provide dual activity, and the catalytic effect is highly pronounced with process intensification using H2O2 and/ or pH alternations. Integration of SCVD, pH and H2O2 was the most effective strategy. Complete degradation of the antibiotics was achieved within minutes with H2O2 (-1000 molar ratio) for both Cu and Ni-surface-coated cavitation reactors compared to lower degradation of-19% for CFX and-37% for CIP using only HC. An excellent enhancement of over 300% for CFX degradation at pH 11 and-170% for CIP degradation at pH 4 was obtained. Huge enhancements in per-pass degradation and cavitational yields (up to 400 times) clearly highlight the utility of the surface-coated cavitation reactors in various applications and for cost-effectiveness.(c) 2023 Institution of Chemical Engineers. Published by Elsevier Ltd. All rights reserved.
Keywords: Hydrodynamic cavitation; Oxidation; pollution; Reactor; Technology; Wastewater treatment

Enhanced disinfection efficiency using Cu vortex diode for providing safe drinking water: devising newer methodologies - Dixit, Divya; Balapure, Kshama; Bhandari, Vinay M. (Environmental Quality Management, 2024)
The present research aims to refine the hydrodynamic cavitation technique with traditional knowledgebase of Ayurveda for more efficient water disinfection and that has huge potential for implementation in real life, especially for substituting the existing chlorination method for drinking water treatment. The study incorporates use of newer copper reactor configuration, employing vortex flow for generating cavitation for the disinfection of water. Elimination of model contaminant, Escherichia coli, with initial concentration of ∼105 CFU/mL of bacteria was used for the disinfection study. Copper vortex diode with a capacity of 1 m3/h was employed as a cavitating device. The cavitation using copper vortex diode gave significantly higher disinfection, over 30%, compared that with conventional vortex diode, with aluminum as material of construction, under similar conditions. Remarkably, the addition of 0.1% betel leaf oil led to an extraordinary 260-fold increase in the rate of disinfection, requiring only a single pass to achieve complete bacteria elimination. Furthermore, a notably high synergistic index of 246.96 was achieved for the process intensification approach using the Cu vortex diode. The cost was substantially reduced by approximately three times to 0.011 $/m3 using the Cu vortex diode compared to the conventional vortex diode. The developed strategy offers significantly enhanced performance, as well as a techno-economical and sustainable solution for drinking water treatment to ensure the provision of safe drinking water. Moreover, the newer methodology can have the advantage of producing no harmful carcinogenic disinfection by-products compared to chemical disinfection processes apart from sustainable alternative to chlorination.